ASSESSMENT OF GENETIC DIVERSITY IN BALOCHI AND RAKHSHANI SHEEP BREEDS OF BALOCHISTAN USING MICROSATELLITE DNA MARKERS - A. Wajid; M. Wasim; T. Yaqub; S. Firyal; M. Tayyab; S. Siddique; T. Hussain (Journal of Animal and Plant Sciences, 2014)
This study was conducted to analyze the genetic diversity and variability of two sheep breeds (Balochi and Rakhshani), from Balochistan province of Pakistan, through the use of 11 microsatellite markers recommended by FAO. All the screened loci were polymorphic and 70 alleles in total were observed in all studied loci with average polymorphic information content equal to 0.57, showing that the microsatellite panel used was highly informative. The result divulged high level of genetic variability in each of the two investigated sheep breeds, allele diversity in Balochi 4.5455 and Rakhshani was 4.0909; gene diversity in Balochi 0.5927 and Rakhshani was 0.6182. High heterozygosity value indicated low level of inbreeding, low or no selection pressure and large number of alleles. Further support in this regard was observed by inbreeding estimate (Balochi FIS = 0.0292 and Rakhshani FIS = 0.0084) in our sheep population. High level of genetic differentiation between Balochi and Rakhshani sheep breeds was evident from high genetic differentiation estimates (FST = 0.1884). The pair wise comparison between both breeds at each locus in term of number of alleles shared (36%, 25/70) reflected the variation between them. The Nei’s genetic distances (DS = 1.3001 and DA = 0.2725) and gene flow (Nm = 1.0767) further indicating the genetic variation between Balochi and Rakhshani sheep breeds. These data depicts the effectiveness of FAO recommended microsatellite markers for estimation of genetic diversity in Balochi and Rakhshani sheep breeds of Pakistan and may be helpful for comparison with other reported data and for better understanding and breed conservation efforts locally and worldwide.
Keywords: Sheep breeds; genetic diversity; microsatellite makers; Balochi breed; Rakhshani breed